2023
DOI: 10.1021/acsphotonics.3c00420
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Characterization of Single-Quantum-Dot Emission Spectra and Spectral Diffusion by Multiparticle Spectroscopy

Abstract: In recent years, quantum dots (QDs) have emerged as bright, color-tunable light sources for various applications such as light-emitting devices, lasing, and bioimaging. One important next step to advance their applicability is to reduce particle-toparticle variations of the emission properties as well as fluctuations of a single QD's emission spectrum, also known as spectral diffusion (SD). Characterizing SD is typically inefficient as it requires time-consuming measurements at the single-particle level.Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
(170 reference statements)
1
1
0
Order By: Relevance
“…The relatively narrow single-QD line widths of 60–80 meV and much broader ensemble line widths (200 meV) are consistent with previous studies on InP-based core/shell QDs . Recent work has confirmed that InP-based core/shell QDs can have narrow single-QDs line widths but also showed that they on average suffer more from spectral diffusion (Figure S8b) and that inhomogeneous broadening is more significant than for CdSe-based QDs . Our measurements in Figure b show narrow single-QD line widths even for core-only InP QDs.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The relatively narrow single-QD line widths of 60–80 meV and much broader ensemble line widths (200 meV) are consistent with previous studies on InP-based core/shell QDs . Recent work has confirmed that InP-based core/shell QDs can have narrow single-QDs line widths but also showed that they on average suffer more from spectral diffusion (Figure S8b) and that inhomogeneous broadening is more significant than for CdSe-based QDs . Our measurements in Figure b show narrow single-QD line widths even for core-only InP QDs.…”
supporting
confidence: 91%
“…29 Recent work has confirmed that InP-based core/shell QDs can have narrow single-QDs line widths but also showed that they on average suffer more from spectral diffusion (Figure S8b) and that inhomogeneous broadening is more significant than for CdSe-based QDs. 30 Our measurements in Figure 3b show narrow single-QD line widths even for coreonly InP QDs. This is encouraging, as it promises the possibility of narrower line widths in InP CQDs with improved surface passivation or engineered electron−phonon coupling.…”
Section: Nanomentioning
confidence: 64%